Diagnosis of elastofibroma - Cuneyt Tetikkurt; Seza Tetikkurt; Nihal Bayar (Canadian Respiratory Journal)
Elastofibroma is a relatively rare soft tissue mass. The lesion is probably reactive and occurs most commonly in the periscapular region. It is a degenerative benign neoplasm with the clinical appearence of a malignant tumour. The present report describes the case of a 70-year-old man with bilateral elastofibroma. The diagnosis was established with needle aspiration biopsy and positron emission tomography/computed tomography. The present case suggests that needle aspiration biopsy and positron emission tomography/computed tomography are highly useful in the diagnosis of this rare, benign tumour.